An Efficient Method for Long‐Term Configurational Stabilization of Chiral Tricyclic Dipeptide via Heterocomplexation Approach. Issue 11 (19th March 2019) - Hu, Xiaoyun; Yin, Zhongyou; Guo, Jianxin; Borovkov, Victor; Shan, Zixing
Abstract: An efficient and practical strategy has been established to enhance the configurational stability of chiral tricyclic dipeptide, which readily undergoes spontaneous racemization under environmental conditions. Complexation of the chiral dipeptide with racemic diols via non‐covalent interaction results in the corresponding heterocomplexes (HCs), which are able to preserve chirality of the dipeptide as long as 24 months. A nearly quantitative recovery of enantiopure dipeptide and racemic diols was achieved by simple treatment of the HCs with a biphasic system of H2 O‐ethyl acetate and subsequent separation from aqueous and organic layers, respectively. This study not only provides a facile and handy method for the configurational stabilization of the chiral dipeptide, but also opens a further prospect for the long‐term chirality preservation of other instable enantiomeric compounds via heterocomplexation approach. Abstract : An efficient and practical strategy has been established to enhance the configurational stability of chiral tricyclic dipeptide via heterocomplexation with chiral diols. A nearly quantitative recovery of enantiopure ( S, S )‐1 and racemic diols was achieved by simple treatment of the heterocomplex with a biphasic system of H2 O‐ethyl acetate and subsequent separation from aqueous and organic layers, respectively.